Soluble TIM3 and Its Ligands Galectin-9 and CEACAM1 Are in Disequilibrium During Alcohol-Related Liver Disease and Promote Impairment of Anti-bacterial Immunity - Riva, Antonio; Palma, Elena; Devshi, Dhruti; Corrigall, Douglas; Adams, Huyen; Heaton, Nigel; Menon, Krishna; Preziosi, Melissa; Zamalloa, Ane; Miquel, Rosa; Ryan, Jennifer M.; Wright, Gavin; et al. (Frontiers in Physiology, 2021)
Background and Aims Immunoregulatory checkpoint receptors (CR) contribute to the profound immunoparesis observed in alcohol-related liver disease (ALD) and in vitro neutralization of inhibitory-CRs TIM3/PD1 on anti-bacterial T-cells can rescue innate and adaptive anti-bacterial immunity. Recently described soluble-CR forms can modulate immunity in inflammatory conditions, but the contributions of soluble-TIM3 and soluble-PD1 and other soluble-CRs to immune derangements in ALD remain unclear. Methods In Alcoholic Hepatitis (AH; n = 19), alcohol-related cirrhosis (ARC; n = 53) and healthy control (HC; n = 27) subjects, we measured by Luminex technology (i) plasma levels of 16 soluble-CRs, 12 pro/anti-inflammatory cytokines and markers of gut bacterial translocation; (ii) pre-hepatic, post-hepatic and non-hepatic soluble-CR plasma levels in ARC patients undergoing TIPS; (iii) soluble-CRs production from ethanol-treated immunocompetent precision cut human liver slices (PCLS); (iv) whole-blood soluble-CR expression upon bacterial challenge. By FACS, we assessed the relationship between soluble-TIM3 and membrane-TIM3 and rescue of immunity in bacterial-challenged PBMCs. Results Soluble-TIM3 was the dominant plasma soluble-CR in ALD vs. HC (p = 0.00002) and multivariate analysis identified it as the main driver of differences between groups. Soluble-CRs were strongly correlated with pro-inflammatory cytokines, gut bacterial translocation markers and clinical indices of disease severity. Ethanol exposure or bacterial challenge did not induce soluble-TIM3 production from PCLS nor from whole-blood. Bacterial challenge prompted membrane-TIM3 hyperexpression on PBMCs from ALD patient’s vs. HC (p < 0.002) and was inversely correlated with plasma soluble-TIM3 levels in matched patients. TIM3 ligands soluble-Galectin-9 and soluble-CEACAM1 were elevated in ALD plasma (AH > ARC; p < 0.002). In vitro neutralization of Galectin-9 and soluble-CEACAM1 improved the defective anti-bacterial and anti-inflammatory cytokine production from E. coli-challenged PBMCs in ALD patients. Conclusions Alcohol-related liver disease patients exhibit supra-physiological plasma levels of soluble-TIM3, particularly those with greater disease severity. This is also associated with increased levels of soluble TIM3-ligands and membrane-TIM3 expression on immune cells. Soluble-TIM3 can block the TIM3-ligand synapse and improve anti-bacterial immunity; however, the increased levels of soluble TIM3-binding ligands in patients with ALD negate any potential immunostimulatory effects. We believe that anti-TIM3 neutralizing antibodies currently in Phase I clinical trials or soluble-TIM3 should be investigated further for their ability to enhance anti-bacterial immunity. These agents could potentially represent an innovative immune-based supportive approach to rescue anti-bacterial defenses in ALD patients.